2007
DOI: 10.1063/1.2771078
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulses in linearly coupled Ginzburg-Landau equations

Abstract: This article presents a brief review of dynamical models based on systems of linearly coupled complex Ginzburg-Landau (CGL) equations. In the simplest case, the system features linear gain, cubic nonlinearity (possibly combined with cubic loss), and group-velocity dispersion (GVD) in one equation, while the other equation is linear, featuring only intrinsic linear loss. The system models a dual-core fiber laser, with a parallel-coupled active core and an additional stabilizing passive (lossy) one. The model gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 50 publications
0
60
0
Order By: Relevance
“…To this end, we consider a complex Ginzburg-Landau model with the cubic nonlinearity (CGL3), for which an analytical chirped-sech localized solution is well known in the one-dimensional (1D) setting [10,11]. While this solution is always unstable, it has been shown that an additional, linearly coupled, dissipative linear equation can lead to its stabilization in coupled-waveguide models, keeping the solution in the exact analytical form [8,12,13]. Selflocalized states in a wide variety of systems described by such coupled linear and nonlinear equations, in both 1D and 2D, was recently discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we consider a complex Ginzburg-Landau model with the cubic nonlinearity (CGL3), for which an analytical chirped-sech localized solution is well known in the one-dimensional (1D) setting [10,11]. While this solution is always unstable, it has been shown that an additional, linearly coupled, dissipative linear equation can lead to its stabilization in coupled-waveguide models, keeping the solution in the exact analytical form [8,12,13]. Selflocalized states in a wide variety of systems described by such coupled linear and nonlinear equations, in both 1D and 2D, was recently discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The field of spatial pattern formation in nonlinear systems has grown significantly in the last decades (see reviews [1][2][3][4][5][6][7][8][9]). In particular, that growth was significantly contributed to by the interest in self-localized states ("solitons") and their stability in pattern-forming systems, both conservative and dissipative ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility was first proposed in the context of nonlinear fiber optics in [1,2]; see also a review in [3]. More recently, a similar scheme was elaborated for the application of gain and the stabilization of solitons in plasmonics [4][5][6], as well as for the creation of stable two-dimensional dissipative solitons and solitary vortices in dual laser cavities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a similar scheme was elaborated for the application of gain and the stabilization of solitons in plasmonics [4][5][6], as well as for the creation of stable two-dimensional dissipative solitons and solitary vortices in dual laser cavities [7,8]. Commonly-adopted models of dual-core nonlinear waveguides are based on linearly-coupled systems of nonlinear Schrödinger (NLS) equations, which include gain and loss terms [3]. One of the advantages provided by these systems for the theoretical analysis is the availability of exact analytical solutions for stable solitons [9].…”
Section: Introductionmentioning
confidence: 99%